The Use of Ibrutinib in Extranodal Marginal Zone Lymphoma of the Ocular Adnexa with Multifocal Disease that is Refractory to Rituximab - Luna, Alexander; Shenouda, Mary (Translation: The University of Toledo Journal of Medical Sciences, 2024)
Tumors of the ocular adnexa been well documented. The most common ocular adnexal lymphoma is extranodal marginal zone B-cell lymphoma (EMZL), with about a quarter of those occurring in the conjunctiva. We present a case with a patient suspected ocular EMZL, confirmed with biopsy. Positron emission tomography (PET) scan was performed to evaluate for distal lesions and the patient was found to have multiple hypermetabolic lesions throughout the body. Treatment with rituximab was initiated, and after four weekly treatments, subsequent PET scan showed that the original hypermetabolic lesions remained and new lesions appeared. Rituximab was stopped and ibrutinib started. After eight months of ibrutinib treatment, PET scan showed that the original hypermetabolic lesions had disappeared. 19 months from initiation of treatment, a new hilar lesion was found. This progressed into bilateral hilar and mediastinal lymphadenopathy, which was seen on PET scan performed 29 months into treatment. These findings remained stable 35 months post-initiation of treatment. The use of ibrutinib in this patient that initially presented with a lesion in the conjunctiva resulted in an initial resolution of the original systemic hypermetabolic regions on PET scan. While more studies are needed on ibrutinib in the treatment of ocular EMZL, physicians should be aware of the presentation of this disease and the range of treatment modalities.